REAKSI PASAR TERHADAP PENGUMUMAN PENCABUTAN PPKM DI INDONESIA - Caesario, Chrismendo Haniel; Wirakusuma, Made Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.07.TAHUN.2023DO - 10.24843/EEB.2023.v12.i07.p19, 2023)
The capital market has an important role for a country's economy because it functions as a means of corporate funding and a place for people to invest in financial instruments. One of the factors that affect the capital market is government policies, for example, the policy of lifting the Implementation of Community Activity Restrictions (PPKM) on December 30, 2022. Based on data from the Jakarta Composite Index (JCI) taken on the Indonesia Stock Exchange (IDX) website,  it shows price fluctuations throughout the announcement period, which is 3 days before and after the announcement. This study aims to obtain empirical evidence related to market reactions to the decision to repeal PPKM in Indonesia. The sample determination method uses the purposive sampling  technique  method. The data usedis secondary data obtained from the Indonesia Stock Exchange throughout the event window. Data analysis techniques using Paired Sample T-Test . Based on the results of purposive sampling , there were 45 sample data used. The results of the analysis show that the average abnormal return on shares during  the period before and after the event is always negative,  it can also be seen from the results of the analysis that  the average Trade Volume Activity (TVA) period before and after the announcement, is negative. This research is able to make an empirical contribution to the development of market efficiency theory as well as additional information related to market reactions in responding to government policies, namely the repeal of PPKM in Indonesia.